Diseño de un módulo de medición inteligente para la lectura del consumo de energía eléctrica mediante tecnología LORA en la fábrica de muebles Jessica. - Denis Cristobal, Abad Berru (2021)
This project focuses on the design of a measurement module for the reading of electrical energy consumption, it is based mainly on not having a system that allows the measurement, transmission and display of data of electrical variables remotely, using LoRa technology for monitoring the consumption of electricity generated by the machines during production, for this an intelligent measurement module is implemented based on LoRa wireless modules and electronic devices that maintain the same communication protocols for the emission, transmission and reception of data, avoiding errors of interpretation and loss of information. With all the technical parameters established, the measurement system maintains a stable connection which allows to have an efficient database, which are stored in the cloud through the configuration of a web server so that the user can observe the results through an HMI screen or through a mobile application that is available for Android systems, also through the measurement module can analyze the consumption made by each of the machines in order to establish usability parameters to generate energy savings. To check the operation of the prototype, field tests were established, obtaining as a result 96% of effectiveness according to the values obtained from the transmission and reception of the data, giving a low percentage of error, which indicates that the information transmitted on energy consumption is acceptable.